UJI VALIDITAS MODUL IPA BERBASIS PROBLEM BASED INSTRUCTION UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA SMP - Febriyanti, Liza; Wulandari, Tabitha Sri Hartati (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2021)
This study was a reasearch and development. The purposed of this research was to design a product and saw the validity of the product. This study produced a Science MODULE based Problem Based Instruction to improve students' critical thinking skills when discussing global warming material. This module presented material and questions based on the Problem Based Instruction learning model that can help students improve their critical thinking skills. The research model used in this study was the ADDIE model. The steps of this research model consists of 5 steps, they were analysis, design, development, implementation, and evaluation. The data was collected by using the validity assessment of the product, which was carried out by assessing the validity test by media experts, material experts, and users, namely teachers and students. The results of this study indicated that the validity test of media experts obtained an average of 87.6% which was stated by valid criteria, the validity test of material experts was obtained an average of 85.35% which was stated by valid criteria, and from users, namely teachers. 92.35% who were stated as very valid criteria and 87.5% of students were stated as valid criteria. Thus it can be concluded that the results of the product validity test in the form of a science module based Problem Based Instruction in global warming material was suitable for use as teaching material for SMP / MTs students because it meets the predetermined criteria.